Bentuk Afiksasi pada Teks Narasi Mahasiswa BIPA: Kajian terhadap Hasil Tulis Mahasiswa BIPA Asal Afghanistan Angkatan Tahun 2021 di Universitas Muhammadiyah Malang - Nazihatun Najiba; Arif Budi Wurianto; M. Isnaini (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The aim of these research is to explain or describe the form and meaning of the affixation used in the narrative text of BIPA students from Afghanistan class of 2021 at University of Muhammadiyah Malang. The method used is qualitative descriptive approach. The data were collected through primary and secondary. The primary data were collected from the result of an essay written by two BIPA Afghanistan college students who are currently studying masters at University of Muhammadiyah Malang through the KNB Scholarship (Kemitraan Negara Berkembang) as evidenced by secondary data in the form of direct observation, which were carried out for 6 months starting 6 September 2021 until 8 march 2022. The result of this study found errors in use of affixation caused by errors in morphonemic process, error in the use of affix, error in the use of basic words, and errors caused by interlingual interference namely errors are due to the influence of B1 (the mother tongue) on B2 (the target language). The invention in this research can be used as evaluation in the BIPA learning process, especially in affixation learning.